PENGARUH KARAKTERISTIK INDIVIDU TERHADAP PENGEMBANGAN KARIR PNS PEJABAT STRUKTURAL PADA KANTOR PEMERINTAH PROVINSI NTB - RINI YULIANDARI; ASRI OKTIANI; ROLI APRIYANSYAH (GANEC SWARA, 2023)
This research aims to see the influence of individual characteristics on the career development of structural civil servant officials at the NTB Provincial Government office. The formulation of the problem in this research is whether individual characteristics influence the career development of structural civil servants at the NTB Provincial Government office ?. This research is quantitative descriptive research. The population of this research is the total number of Civil Servants in the regional government offices of West Nusa Tenggara Province who occupy structural positions, namely 1,027 people. The sample was taken using the Slovin formula, so the sample size was 91.12 rounded up to 91 people. Simple multiple linear regression analysis, T-test, and correlation coefficient are the data analysis methods used. The results of the research that has been conducted show that the individual characteristics variable has a positive influence on career development. So it can be concluded that the proposed research hypothesis is completely accepted.